The characteristics of the resource needs of innovative businesses - Köpeczi-Bócz, Tamás; Lőrincz, Mónika (Acta Agraria Debreceniensis, 2016)
Every university was funded in different historical periods with particular feature, particular political system, particular proprietory structure and particular economic background, which characterised the particular era. The historical antecedents considerably influenced the situation and role of the institutions as well as the course of their development. Although they had common features but their spatial projections are very dissimilar. In the 19th and 20th century Hungarian history – in the periods of economic integration with the modification of political system and transformation of the social background – the economic and social functions of tertiary education underwent considerable changes, which started to accomplish by the second half of the 20th century and the early 21st century. To moderate regional disparities, European and Hungarian regional development policy considers particular importance to the economic structure of the regions and their potential to be reformed, which is one of the corner stones of compatibility. Considering the more and more diversifying functions of universities, the question is, which factor is more significant; tertiary education or the relation between the sectors of national economy. The possible correlations we presented through the economic structure and the transformation of tertiary education functions of the integration periods.